KELIMPAHAN JENIS CORBICULA POSSOENSIS DAN MELANOIDES GRANIFERA (MOLUSKA) DI DANAU POSO, SULAWESI TENGAH - SILUBA, MUSTARIM (Research Center for Biology-Indonesian Institute of Sciences, 1987)
MUSTARIM SILUBA. 1987.Species abundance Corbicula possoensis and Melanoides granifera Mollusca) in Poso Lake, Central Sulawesi.Berita Bioiogi 3(7): 317 - 320. Corbicula possoensis and Meianoideu granifera are the two dominant species among 18 species of the mollusca that occured in poso Lake.The highly abundance of these two species distributed among three habitat types, i.e. sandy. mudsand, and gTavelly habitat. The study showed that the abundance of C. possoensis is 126,66/m2 in